Design of Electrostatic Unipotential Lens Accelerating And Decelerating Operated Under Finite And Infinite Magnification Conditions - Mohmmed, Intiha`A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Theoretical study computerized has been carried out in field electron optics , to design electrostatic unipotential lens , the inverse problem is important method in the design of electrostatic lenses by suggesting an axial electrostatic potential distribution using polynomial function. The paraxial â€“ray equation is solved to obtain the trajectory particles that satisfy the suggested potential function. In this research , design electrostatic unipotential lens three-electrode accelerating and decelerating L=5 mm operated under finite and infinite magnification conditions. The electrode shape of the electrostatic lens was then determined from the solution of the Laplace’s equation’s. the results showed low values of spherical and chromatic aberrations which are considered as good criteria for good design. `